Hubungan Lagu Srikandi dan Motivasi Reflektif Inspirasi terhadap Mindset Wanita Bersemangat Wirausaha - Pranoto, Henry Susanto; Sitepu, Rismawati Br; Soeparto, Wahyudi Henky; Subagio, Hartono (Universitas Islam Tribakti Lirboyo Kediri, 2024)
As an effort to optimize the function and role of women, researchers conducted a descriptive study to determine the relationship between the influence of the song